Flank bulge following supracostal percutaneous nephrolithotomy: A report of 2 cases - Lantz, Andrea G. (Canadian Medical Association, 2013)
Damage to intercostal nerves during surgical procedures has been associated with a postoperative flank bulge, due to denervation of the anterolateral abdominal wall musculature. This complication has not been reported following percutaneous nephrolithotomy (PCNL). We are aware of 3 cases, but have details on 2 cases of postoperative flank bulge following supracostal PCNL which are reported here. We also suggest how this complication could potentially be minimized.